PENGEMBANGAN KARIR DAN KOMPETENSI PERWIRA TNI (TENTARA NASIONAL INDONESIA) DALAM MISI PERDAMAIAN PBB: STUDI KASUS INDONESIA - triadi murwanto (Jurnal Doktor Manajemen (JDM), 2019)
The current strategic environment in the world shows that there is a greater potential for intrastate conflict, especially in third world countries. The United Nations as a world body has held a UN Peacekeeping Mission as an instrument to create peace in countries which undergo multidimensional conflict. Indonesia has sent its personnel in the UN Peacekeeping Mission since 1957 through the sending of the 1st Garuda  Contingent to the UNEF Mission in Sinai. At present Indonesia has sent a Garuda contingent in various UN Peacekeeping regions in the world. The involvement of TNI personnel in the UN Peacekeeping Mission has continued to increase from year to year. But the increase in the number of TNI personnel involved in the UN Peacekeeping Mission has not been accompanied by an increase in the number of middle / high ranked TNI officers who are able to hold strategic positions at the UN Peacekeeping Mission. This paper aims to convey a view on the career development of TNI Officers in the UN Peacekeeping Mission. This research uses qualitative methods through literature studies and interviews. The findings indicate the need to synchronize the system of career development and education for TNI Officers in the UN Peacekeeping Mission in order to have a competitive advantage in competing to hold some strategic positions in the UN Peacekeeping Mission.